Child Sexual Abuse, Self-esteem, and Delinquent Behaviors During Adolescence: The Moderating Role of Gender - Gauthier-Duchesne, Amélie (Journal of interpersonal violence, 2022)
To reflect the complex phenomena of child sexual abuse (CSA), studies should examine possible gender specificities and explore potentially explanatory mechanisms. The current study aimed to test the moderating effect of gender in the mediated relationship between CSA, self-esteem, and delinquency during adolescence. A moderated mediation model was tested among a representative sample of 8,194 high school students (57.8% girls and 42.2% boys) age 14 to 18 in the province of Quebec in Canada. Results showed that self-esteem has an indirect effect on the relationship between CSA and delinquency. Gender (being a boy) was associated with a higher level of self-esteem and an increased risk of delinquent behaviors. Among victims of CSA, boys reported lower levels of self-esteem than girls, which was associated with an increased risk of displaying delinquent behaviors. Self-esteem may be an important target of intervention for sexually abused youth, especially for boys. Focusing on promoting positive self-esteem may also reduce the risk for male adolescents struggling with the deleterious consequences of delinquency.